Linguistic game elements in food advertising - Naumenko, Nataliia; Stelmakh, R. (My University, 2012)
This article shows the results of game elements ’ analysis in Ukrainian advertising for foodstuff. There was confirmed that language component is cardinally important in creating a good and expedient image of an advertised product, deprived of any kind of contradiction. Particularly, the main factor in achieving this goal is the word game (like puns, rhymes, or alliteration).
Keywords: foodstuff; culture; word game; продукты питания; культура; игра в слова; продукти харчування; гра в слова; кафедра гуманітарних дисциплін